PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL DAN AKSESIBILITAS LAPORAN KEUANGAN TERHADAP TRANSPARANSI PENGELOLAAN KEUANGAN DAERAH PADA PEMERINTAH ACEH - Arief, Susilo; Suparno, Suparno (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This study aims to determine the effect of the effectiveness of internal control and accessibility of financial reports on the transparency of regional financial management in the Aceh government. In this study, the data used is secondary data. The sample selection technique uses Non-Probability Sampling with the census method, where the sample is taken from the entire research population of as many as 46 SKPA with two respondents for each SKPA. The data analysis method used is multiple linear regression analysis which will be carried out using SPSS software. The results of the study show that 1) the effectiveness of internal control and the accessibility of financial reports simultaneously have a significant effect on the transparency of financial management in the Aceh Government. 2) The effectiveness of internal control has a negative and significant effect on the transparency of financial management in the Aceh Government. 3) Accessibility of financial statements has a negative and significant effect on the transparency of financial management in the Aceh Government.